Statistical Tools Applied in the Characterisation and Evaluation of a Thermo-Hygrometric Corrective Action Carried out at the Noheda Archaeological Site (Noheda, Spain) - Miguel Ángel Valero; Paloma Merello; Ángel Fernández Navajas; Fernando-Juan García-Diego (Sensors, 2014)
The Noheda archaeological site is unique and exceptional for its size, and the quality and conservation condition of the Roman mosaic pavement covering its urban pars. In 2008 a tent was installed as protection from rain and sun. Being of interest to characterise the microclimate of the remains, six probes with relative humidity and temperature sensors were installed in 2013 for this purpose. Microclimate monitoring allowed us to check relative humidity differences resulting from the groundwater level, as well as inner sensors reaching maximum temperatures higher than the outdoors ones as a consequence of the non-ventilated tent covering the archaeological site. Microclimatic conditions in the archaeological site were deemed detrimental for the conservation of the mosaics. Thus, in summer 2013, expanded clay and geotextile were installed over the mosaics as a corrective action. The outcomes of this study have proven the effectiveness of this solution to control temperature and relative humidity, helping to configure a more stable microclimate suitable for preservation of the mosaic.